REFRACTIVE ERRORS IN CHILDREN ATTENDING OUT-PATIENT DEPARTMENT OF OPHTHALMOLOGY, KHYBER TEACHING HOSPITAL, PESHAWAR: Refractive errors in Children - Sethi, Sadia; Sethi, Mohammad Junaid; Hussain, Ibrar; Khan, Tajamul (Pakistan Armed Forces Medical Journal, 2008)
Objectives: The objectives of the study were to estimate the occurrence of refractive errors in children age up to 15 years, attending outpatient department of Ophthalmology Khyber Teaching Hospital Peshawar, identify their types and provide them with glasses.Study design: A repetitive hospital based study.Place and duration of study: Eye Department, Khyber Teaching Hospital, Peshawar, where study was conducted from 1st October 2006 to 31st March 2007. Patients and Methods: All children age upto 15 years with refractive errors coming to Outpatient Eye Department Khyber Teaching Hospital from 1st October 2006 to 31st March 2007 were included in this repetitive study. Detailed ocular examination was performed on each patient. It consisted of visual acuity testing, pupillary reaction, ocular motility examination, anterior segment examination and direct ophthalmoscopy. The refractive error was noted with type and the patients who needed glasses were provided free glasses. Results: Out of 2340 children 300 (12.8%) had refractive error. Mean age of children was 6 years. Forty five (15%) children were below 3 years, 180 (60%) were between 3-10 years and 75 (25%) were between 11-15 years. One hundred thirty five (45%) were male and 165 (55%) were female. Myopia occurred in 85 (28.33%) Hypermetropia occurred in 75 (25%) and astigmatism in 140 (46.67%) children. Myopic astigmatism occurred in 19 (6.3%), hypermetropic astigmatism in 38 (12.7%) and mixed astigmatism in 83 (27.7%) children. Free glasses were provided to all the children. Anisometropia occurred in 19 (6.3%) patients. Bilateral amblyopia occurred in 10 (3.3%) patients. Unilateral amblyopia occurred in 10 (3.3%).Conclusion: This study showed that the uncorrected refractive error was a major problem among children. Females were almost equally affected as males. Astigmatism was the most common problem. Treatment for refractive errors is perhaps the simplest and most effective form of eye care.